Differential regulation of the release of tumor necrosis factor-α and of eicosanoids by mast cells in rat airways after antigen challenge - Aryene Goes Trezena; Zilma Lucia da Silva; Ricardo Martins Oliveira-filho; Amilcar Sabino Damazo; Anita Hilda Straus; Helio Kiyoshi Takahashi; Sonia Maria Oliani; Wothan Tavares de Lima (Hindawi Limited, 2003)
Background: Rat trachea display a differential topographical distribution of connective tissue mast cells (CTMC) and mucosal mast cells (MMC) that may imply regional differences in the release of allergic mediators such as tumor necrosis factor-α (TNF-α) and eicosanoids.